Constitutionalism human rights and the rule of law - "Ramachandran,Raju (ed.)" (Delhi, 2005)
Soli Jahangir Sorabjee was the attorney general for India from April 1998 to May 2004. He was the solicitor general of India Addl. Solicitor Gen. of India in late seventies. He started legal practice in 1953 and was designated Senior Advocate Supreme Court of India in 1971.Mr. Sorabjee mainly practices in the field of constitutional and administrative law. He was the member of the National Commission to review the working of Constitution. About Author : Mool Chand Sharma presently director, National Law Instituet University, Bhopal. Concurrently professor, law faculty, Delhi University. Has published extensively including three books on issues relating to law & poverty, constitutional jurisprudence and human rights. Has been research advisor to National Human Right Commission, National Consultant to UGC, Senior consultant to Ford Foundation and many other organisations. Raju Ramchandran is a senior advocate of the supreme court and a former additional solicitor general of India. He is the author of Changing Profession, Changing Ethics (2004). He is also revising author of B.R Agarwala`s Supreme court practice and procedure (2002)
Keywords: Constitutional law-India